Հրաչյա Աճառյան. կյանքը և գիտական գործունեությունը - Գ. Մ. Մխիթարյան (ՀՀ ԳԱԱ Հ. Աճառյանի անվ. լեզվի ինստիտուտ)
Статья посвящается жизни и научной деятельности великого армянского ученого Р. Ачаряна. Его фундаментальные труды являются исходными и вехой в области арменоведения и сравнительного изучения языков не только для нынешних, но и для будущих поколений армянских лингвистов и филологов. Как упомянул академик Г. Джаукян, достоверно можно отметить следующее – пока существует лингвистика, будет существовать и арменоведение, пока существует арменоведение, Г. Ачарян будет жить вечно. G. M. Mkhitaryan, H. Acharyan: Life and Activity.- The article is dedicated to the life and scientific activities of the great Armenian scientist G. Acharyan. His fundamental works are the starting point and milestone in the field of Armenology and comparative study of languages, not only for current, but also for future generations of Armenian linguists and philologists.As it was mentioned by academician G. Jahukyan, the following can be noted authentically: as long as linguistics exists, Armenology will exist,as long as Armenology exists, G. Acharyan will live forever.
Keywords: Կենսագրություն; Լեզու և գրականություն